Analisis Kebutuhan, Daya Tarik Dan Keamanan Konsumen Terhadap Pendapatan Pedagang (Studi Kasus Pada Pasar Way Jepara Lampung Timur) - Firmaliana, Ema; Yateno, Yateno (Universitas Muhammadiyah Metro, 2023)
ABSTRACT This research was conducted to determine the effect of need, attractiveness, and security on the income of traders. The scope of this research includes the independent variables where Need (X1), Attractiveness (X2), and Security (X3). While the dependent variable (dependent variable) is the income of traders (Y), this research is a type of quantitative research with a survey. The method taken to determine the sample in this study is to use a purposive sampling technique. The results of this study indicate that the need has a significant effect on the income of traders. Attractiveness has a significant effect on the income of traders. Security has a significant effect on traders' income. Need, attractiveness, and security together have a significant effect on the income of traders. Keywords: need, attractiveness, security, income